3D Cell Culture: Conducting Polymer Scaffolds for Hosting and Monitoring 3D Cell Culture (Adv. Biosys. 6/2017). Issue 6 (June 2017) - Inal, Sahika; Hama, Adel; Ferro, Magali; Pitsalidis, Charalampos; Oziat, Julie; Iandolo, Donata; Pappa, Anna‐Maria; Hadida, Mikhael; Huerta, Miriam; Marchat, David; Mailley, Pascal; Owens, Róisín M.
Abstract : In article number1700052, Sahika Inal, Róisín M. Owens, and co‐workers present a conducting polymer scaffold, which supports three‐dimensional co‐culture of multiple cell types due to its biocompatibility, porous architecture, and tissue‐like elasticity. The growth of cells/tissue inside the conducting polymer scaffold affects its electrical properties, which is a parameter used to monitor cell growth. The scaffold thus plays a dual role: hosting and monitoring cells. The cover was designed by Heno Hwang, scientific illustrator, King Abdullah University of Science and Technology.